The Role Natural Tafakur Activities In Improving The Faith of Student Islamic Boarding School Jagad ‘Alimussirry - Maghfiroh, Nur Lailatul (http://jagadalimussirry.com/, 2020)
Tafakur is an activity of internal thinking that includes the processes and knowledge possessed by individuals in the cognitive aspect, involving feelings and emotions in the affective aspect, and specifically in this case the spiritual aspect. In the modern era, in increasing the faith of students, it does not have to be done with the activities of reciting the Islamic boarding school. The students' faith can be improved by learning or reciting the Qur'an in the wild. Learning in outside of Islamic boarding school can bring student integrated with nature. Nature will open the horizons of student's wider view. This method of learning with nature is expected to establish harmony between learning material inside Islamic boarding schools and outside Islamic boarding schools or that can be called natural meditation. The nature recitation activities to increase the students' faith carried out by Islamic Boarding School Jagad Alimussirry include material giving activities by presenters who are experts in their fields, nature exploring, obligatory prayers or sunnah in congregation, the cult of each group, and the night devotions.